STRATEGI BADAN AMIL ZAKAT KABUPATEN SAMBAS DALAM DISTRIBUSI ZAKAT SEBAGAI UPAYA MENGENTASKAN KEMISKINAN - Arpiati; Munadi; Arnadi (CBJIS: Cross-Border Journal of Islamic Studies, 2022)
This study aims to determine (1) Baznas Kabupten Sambas in the distribution of zakat as an effort to alleviate poverty (2) The impact of distribution of zakat funds as an effort to alleviate poverty in Sambas Regency. The approach used in this research is a qualitative approach. The method used in this research is descriptive qualitative analysis. Descriptive method is intended that researchers explain the strategy and impact of distribution of zakat by Baznas Sambas Regency in alleviating poverty. This research is a field research with research setting in Baznas, Sambas Regency. Data collection techniques using interviews, documentation, and observation. Data sources consist of primary data and secondary data. The data analysis technique adopted by the researcher is data analysis, data reduction, data categorization, data interpretation and conclusions. Meanwhile, to test the credibility of the data, the researchers extended the observation time, and increased persistence in research. The results of this study indicate that the existence of Baznas in Sambas Regency is quite beneficial for the community. This institution has collaborated with the government in tackling increasingly complex social and poverty problems, especially for the mustahik, so that they are able to grow and develop the community with a persistent, professional entrepreneurial spirit and make them muzzaki. Some of the strategies that have been planned by BAZNAS in Sambas Regency have been implemented well and some have not been implemented, namely poverty programs that directly touch the poor through productive programs. The BAZNAS program in Sambas Regency has poverty programs such as: productive businesses, house renovations, and scholarships. However, the program encountered problems with the lack of zakat funds collected. BAZNAS Sambas Regency has implemented productive zakat even though it is still not evenly distributed and is more distributed through consumptive zakat whereas through productive zakat, it is very influential in reducing poverty. With the existence of zakat where the distribution of ZIS funds is given to mustahik so that the person concerned can be independent and develop his business, it is an alternative that needs to be continuously developed for community empowerment. However, care is needed in selecting Mustahik candidates in the hope that the funds will be used for their real interests. And as an alternative to the distribution of ZIS funds for productive businesses, the prospects are quite promising and significant in the future.